Stiff person-like syndrome: an unusual presentation of pituitary macroadenoma with panhypopituitarism - Goh, Kian Guan; Yusof Khan, Abdul Hanif Khan; Nasruddin, Azraai (Karger, 2022)
Pituitary adenoma can manifest as pituitary hypofunction, which can cause symptoms of panhypopituitarism. Commonly, symptoms of hormonal deficiencies such as lethargy, weight change, cold intolerance, and sexual dysfunction are reported. Optic chiasmal compression leads to visual field changes and the discovery of the pituitary lesion. However, limb stiffness is a rare presentation of hypopituitarism, especially hypocortisolism. We report a 68-year-old man who presented with progressive lower limb stiffness associated with truncal instability mimicking a stiff person syndrome (SPS). Hypoglycaemia and hyponatraemia prompted the discovery of pituitary macroadenoma with panhypopituitarism. Investigation showed pituitary macroadenoma on magnetic resonance imaging with hypocortisolism, hypothyroidism, and hypogonadotropic hypogonadism. After initiating hydrocortisone replacement, the patient had complete resolution of lower limb stiffness with no permanent neurological sequelae. It is postulated that hypocortisolism and hyponatraemia disrupt the metabolic function of muscle leading to stiffness. As a result, lower limb rigidity, flexion deformities, and pain are more common. Differentiating adrenal insufficiency associated with rigidity and SPS is important as the response to treatment for both conditions differs. Prompt treatment leads to fast resolution and prevents contractures in adrenal insufficiency-associated rigidity. Thus, recognizing limb rigidity as the first presentation of hypopituitarism is important to avoid long-term complications.